Amino acid mediated mesopore formation in LTA zeolites. Issue 6 (25th January 2016) - Chen, Zhuwen; Zhang, Jian; Yu, Bole; Zheng, Guangchao; Zhao, Jing; Hong, Mei
Abstract : Amino acids, self-assembled in situ via hydrogen bonding, have been used to synthesize mesoporous zeolites without a calcination step. Abstract : Mesoporous LTA zeolites have been hydrothermally synthesized by using amino acids as a mesoporogen. Amino acids of carnitine, lysine, or their salt derivatives were able to generate disordered mesopores of 10–20 nm within single crystalline LTA zeolites. Unlike other mesopore generating templates such as surfactants or polymers, the amino acid templates could be easily removed by washing with water, eliminating the energy-intensive calcination step. A possible crystallization process involving three-dimensional assembly of amino acid templates via hydrogen bonding and electrostatic interaction was proposed, as it was found that hydrogen bonding is crucial in hierarchical structure generation, and that hydroxyl group shielded acetyl carnitine yielded no mesopores. The obtained hierarchically mesoporous LTA zeolites exhibited a remarkably higher adsorption capacity (264 mg g −1 ) for catalase enzyme, and retained greater enzyme activity (>90%) than did conventional LTA.